Forty women: unseen women of the Bible from Eden to Easter - Clarke, Ros (IVP, 2021)
"The first witnesses to the resurrection were not men, but women - and without women, the Easter story would not have happened at all. These hidden voices of the Bible's story are found through the Old Testament and the New Testament. In this daily Lent devotional for 2022, join Ros Clarke as she uncovers the women of the Bible who are essential to the Easter weekend. From Eve to the Shummamite, and from Deborah to Ruth, Forty Women will open your eyes to the power of the gospel. Exploring a different character each day to take you from Ash Wednesday to Easter Sunday, Forty Women is an uplifting and inspirational look at what we can learn from the different women of the Bible."